Asarum wannanense, a new species of Aristolochiaceae from Southern Anhui, Eastern China - Peng, Hua-Sheng; Yin, Min-Zhen; Wang, De-Qun; Liu, Hao; Liu, He-Ling; Huang, Lu-Qi (Phytotaxa, 2023)
Asarum wannanense Lu Q. Huang & H. S. Peng, a new species from southern Anhui, eastern China, is described and illustrated. This new species is similar to A. magnificum Tsiang ex C. Y. Cheng et C. S. Yang, but the prominent morphological difference lies in the special calyx tube. The calyx tube of A. wannanense is constricted at the middle and upper part, with an orifice ring of ca. 4 mm wide. The orifice ring and the floral opening have elongated into a secondary calyx tube, with transversely corrugate characteristics.